(untitled) (American International Journal of Economics and Finance Research, 2020)
This study aims to test the validity of the PIH for Ghana using aggregate annual data of GDP per capita and household consumption expenditure per capita from 1971 to 2017. The data used were taken from UN statistics. The PIH holds that the income a consumer expects to persist throughout his or her life is what determines their consumption. Earlier studies have shown that the PIH implies the magnitude of the revision in permanent income arising from innovation in the income process is proportional to the magnitude of the revision in consumption arising from the same innovation. This study tests this implication. Innovation in the income process here is the part of the income process that could not be forecasted. The study generates the innovation in the income process by estimating an ARMA model for income and then estimates a consumption equation by OLS using the consumption variable and the generated innovation in income variable. The study finds that the magnitude of the revision in permanent income arising from the innovation in income is larger than the magnitude of the revision in consumption resulting from the same innovation. This implies consumption response to changes in income is smaller than what the PIH predicts. This result is taken as evidence that the PIH does not hold for Ghana.